ASSESSMENT OF SUBFASCIAL PRESSURE CHANGES IN INJURED WITH POLYSTRUCTURAL GUNSHOT WOUNDS TO THE LOWER EXTREMITY - Strafun, S.S.; Shypunov, V.H.; Laksha, A.M.; Borzykh, N.O.; Tsymbaliuk, Ya.V.; Sydorova, N.M. (World of Medicine and Biology, 2022)
The purpose of the study was to study the changes in subfascial pressure in wounded with gunshot wounds to the lower extremity during the first 24 hours after injury. Data of 137 measurements of subfascial pressure in osteofascial compartments of the damaged segment, obtained in 128 servicemen with gunshot wounds, were analyzed. In gunshot fractures of the lower extremities, the average level of subfascial pressure increases in the period from 6 to 12 hours after injury by 35.8 % (p=0.0111) with a total rise for the first 24 hours after injury from 29.9±11.4 to 47.2±8.8 mm Hg (p=0.0005), but remains statistically similar for the periods 6–12 and 12–24 hours after injury. In cases with soft tissue gunshot wounds to the lower extremity, the average value of subfascial pressure progressively increases (after 6–12 hours from injury by 22.9 %, after 12–24 hours – by another 39.4 %, р=0.0240 and р=0.0076, respectively). Isolated tangential soft tissue gunshot wounds to the lower extremity without fascia lesion do not have any statistically significant effect on the subfascial pressure levels.